Dupilumab Provides Rapid and Sustained Improvement in SCORing Atopic Dermatitis Outcomes in Paediatric Patients with Atopic Dermatitis - Andreas Wollenberg; Danielle Marcoux; Jonathan I. Silverberg; Valeria Aoki; Eulalia Baselga; Haixin Zhang; Noah A. Levit; Alain Taieb; Ana B. Rossi (Medical Journals Sweden, 2022)
This post hoc analysis examined SCORing Atopic Dermatitis (SCORAD) outcomes in 471 paediatric patients (children age 6-<12 years, n = 304; adolescents age 12-<18 years, n = 167) with atopic dermatitis treated with dupilumab, ± topical corticosteroids, in two 16-week phase 3 randomized controlled trials and a 1-year interim data cut of a subsequent open-label extension study. Paediatric patients treated with dupilumab (± topical corticosteroids) had significantly lower SCORAD, objective SCORAD (o-SCORAD), and individual SCORAD components from week 3 to 16 compared with placebo (± topical corticosteroids) in the randomized controlled trials. The results were sustained or continuously improved over 1 year of open-label treatment with dupilumab ± topical corticosteroids. SCORAD-50 was achieved in almost all patients (91.3-91.8%) by week 52 with continued dupilumab treatment across age groups. Almost all (>  86%) patients achieved mild or absent pruritus and sleep loss at week 52. In conclusion, dupilumab ± topical corticosteroids resulted in rapid and significant improvements in all aspects of SCORAD analysed, and the results were sustained over 1 year.